Myocardial dysfunction caused by MyBPC3 P459fs mutation in hypertrophic cardiomyopathy: evidence from multi-omics approaches and super-resolution imaging - Wu, Yupeng; Zhang, Yuzhu; Zheng, Qirui; Wang, Qiyuan; Fang, Xingyu; Zhu, Zaihan; Lu, Jing; Sun, Dandan (Frontiers in Cardiovascular Medicine, 2025)
IntroductionMutations in the sarcomere protein, particularly in cardiac myosin binding protein C gene (MyBPC3), were the most frequent genetic cause of hypertrophic cardiomyopathy (HCM). The pathogenic MyBPC3 P459fs mutation has been reported in HCM patients. However, there was limited knowledge of the structure–function relationships and potential pathways in clinical HCM with MyBPC3 P459fs mutation.MethodsWe used multi-omics approaches and super-resolution imaging to explore the effects of MyBPC3 P459fs mutation on humans and cells. HCM patients carrying MyBPC3 P459fs mutation (MyBPC3-P459fs HCMs) and healthy controls (HCs) were evaluated for myocardial function using both conventional and advanced echocardiography. In parallel, H9C2 myocardial cells infected with either MyBPC3 P459fs mutation (P459fs cells) or its wild type (WT cells) were investigated for myocardial fiber formation and the potential pathways behind this using super-resolution imaging and metabolomics and proteomics.ResultsFirst, conventional and advanced echocardiography showed that MyBPC3-P459fs HCMs exhibited left ventricular diastolic and systolic dysfunction. Subsequently, super-resolution imaging indicated that P459fs cells formed fewer and shorter myocardial fibers in the cytoplasm compared to WT cells. Moreover, our metabolomic and proteomic data suggested several key components of mitochondrial membrane integrity, myocardial remodeling, myocardial energy metabolism, oxidative stress, inflammation, and actin binding capacity were significantly altered in response to P459fs mutation.ConclusionsThis investigation indicated myocardial dysfunction and myocardial fiber disarray in clinical HCMs with MyBPC3 P459fs mutation and added potential pathways underlying this. These findings provided a link between the observed structural and functional disorders in MyBPC3 P459fs mutation and its onset of HCM pathogenesis and might have a significant translational contribution to effective treatment in HCM patients with MyBPC3 P459fs mutation.